2019
DOI: 10.1002/bjs.11295
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of recurrence pattern after resection for pancreatic cancer

Abstract: Background: Initial recurrence mapping of resected pancreatic ductal adenocarcinoma (PDAC) could help in stratifying patient subpopulations for optimal postoperative follow-up. The aim of this systematic review and meta-analysis was to investigate the initial recurrence patterns of PDAC and to correlate them with clinicopathological factors.Methods: MEDLINE and Web of Science databases were searched systematically for studies reporting first recurrence patterns after PDAC resection. Data were extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 107 publications
(255 reference statements)
7
106
0
1
Order By: Relevance
“…It may also be speculated that perivascular SMA stranding is a morphological correlate of very pronounced perineural invasion. Perineural invasion is well-known as one of the main causes of local tumor recurrence and metastasis and was demonstrated as one of the major prognostic parameters in PDAC [21][22][23]. In the current study, perivascular SMA stranding qualified as an independent prognostic factor, stronger than established prognostic parameters like ASA score, N status, lymphovascular invasion or R status.…”
Section: Discussionmentioning
confidence: 47%
“…It may also be speculated that perivascular SMA stranding is a morphological correlate of very pronounced perineural invasion. Perineural invasion is well-known as one of the main causes of local tumor recurrence and metastasis and was demonstrated as one of the major prognostic parameters in PDAC [21][22][23]. In the current study, perivascular SMA stranding qualified as an independent prognostic factor, stronger than established prognostic parameters like ASA score, N status, lymphovascular invasion or R status.…”
Section: Discussionmentioning
confidence: 47%
“…After the radical resection of pancreatic cancer, approximately 80% of patients would develop recurrence (3). A meta-analysis showed that the weighted median rate of initial recurrence in the liver after resection of pancreatic cancer was 26.5% (5). Pancreatic cancer has a poor prognosis for postoperative recurrence, especially liver recurrence (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of a risk stratification model may help clinicians to design personalized treatment programs for different patients. Previous studies have proposed various risk stratification models for the diagnosis, prognosis, and recurrence of pancreatic cancer, which exhibited better efficiency than the classical TNM stage (43)(44)(45). The rapid development of sequencing techniques has enabled the access to multi-omics data and high-quality clinical information through different databases, such as TCGA, ICGC, and Gene Expression Omnibus (17,46,47).…”
Section: Discussionmentioning
confidence: 99%